Plant blindness: A focus on its biological basis - Achurra, Ainara (Frontiers in Education, 2022)
Plant blindness or the inability to see plants in one’s everyday life is a complex phenomenon in the field of science education. Here I review a forgotten aspect in plant blindness: how human cognitive processes such as perception or memorization of plants are related to plants’ inherent biological features (e.g., being green). Grounded on that knowledge, I reflect about effective practice in plant science education, from which two major recommendations emerge. I conclude that only when we under-stand human-plant relationships will we know how to enhance teaching and learning about plant science.